Pengaruh Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Puzzle Terhadap Hasil Belajar Siswa Pada Pembelajaran Matematika Kelas 2 SD - Inas Fauziah Farda; Nurrohmatul Amaliyah (Elementary Teacher Education Program, Majalengka University, 2023)
Classical lecture and question and answer methods are mostly chosen by teachers. As a result, students are less enthusiastic in following the lesson and the classroom atmosphere looks inactive. To improve students' learning outcomes, a learning innovation based on the STAD type cooperative learning model is needed. The purpose of this study was to analyze the effect of the STAD type cooperative learning model assisted by Puzzle Media on student learning outcomes in Grade 2 mathematics learning. This research uses quantitative research using experimental methods. The design form used in this research is true experimental. In this study the research subjects were divided into two groups, namely the control class group and the experimental class group. Of the two classes, the control class and the experimental class were determined, class II A was selected as the experimental class and class II B was selected as the control class. The technique used in collecting data in this study used a test instrument. The results of this study are the average of the experimental class which is 70, 17 and the control class is 57, 00, from these results there is a significant difference in learning outcomes which indicates the effect of the STAD type cooperative learning model as an effective learning innovation that can be applied so that learning is fun for students.